A rare presentation of supraclavicular schwannoma (Indian Journal of Case Reports, 2020)
Schwannomas or neurilemmomas are benign tumors that arise from Schwann cells that surround the peripheral, cranial, or autonomic nerve sheaths. These are slow-growing, benign, encapsulated tumors that arise from the proliferating Schwann cells, encompassing the nerve sheath. About 25–45% of the schwannomas are found in the head-and-neck region. These tumors can arise from any of the cranial, peripheral, or autonomic nerves and constitute <1% of the tumors seen in the head-and-neck region. In the present case, the tumor was in the lateral group, localized to the right-sided supraclavicular region, and originating from the cervical or brachial plexus. We present the case of a 44-year-old gentleman who presented with a right-sided supraclavicular swelling for 2 months, which initially was thought to be a lymph node mass but which turned out to be a schwannoma on the pathological and radiological diagnosis.